BASED ON IMPROVED ACO WELDING JOINT OPTIMIZATION ANALYSIS - ZHANG ShengYue; QING Li; FENG QiuXia; ZHANG YuDong (Jixie qiangdu)
For reasonable planning of commonly used in the process of equipment manufacturing T-type pipe ring joint Welding path. This paper puts forward a kind of based on finite element Simufact. Weldingand Matlab simulation platform,the introduction of the constraint factors and improved pheromone update rule,to improve the traditional ant colony algorithm,in order to improve the update efficiency of pheromone of ant colony algorithm,and enhance the path of the algorithm in the continuous space search ability. The method to establish the T-type pipe ring joint welding simulation,and analyzes its corresponding welding path respectively,the results show that compared with the traditional ant colony algorithm,based on improved ant colony algorithm of welding path not only saves time resources,and reduce the waste of wire material. Parameters and condition,the welding efficiency increased by 7. 79%,compared to the 3-D welding path Movement distance,fell by6. 31%,and to improve the reliability of 2. 92%. As a result,the method for optimization of T-type pipe ring joint welding path is effective and feasible.